A Single Dose of ViperfavTM May Be Inadequate for Vipera ammodytes Snake Bite: A Case Report and Pharmacokinetic Evaluation - Tihana Kurtović; Miran Brvar; Damjan Grenc; Maja Lang Balija; Igor Križaj; Beata Halassy (Toxins, 2016)
ViperfavTM is a commercial F(ab’)2 antivenom prepared against European vipers venom. It is safe and effective for treating envenomation caused by Vipera aspis and Vipera berus. Therapeutic efficacy for treating Vipera ammodytes ammodytes (V. a. ammodytes) envenoming has not been yet described, although protective efficacy has been demonstrated in preclinical studies. We report on a 32-year-old man bitten by V. a. ammodytes who was treated with Viperfav™. Viperfav™ promptly reduced local extension and improved systemic pathological signs, but 24 h after the incident a recurrence of thrombocytopenia occurred despite a favorable pharmacokinetic profile with systemic clearance (1.64 (mL·h−1)·kg−1) and elimination half-life (97 h) among the highest ever reported. The recommended dose of Viperfav™ for V. aspis and V. berus bites may be inadequate for serious V. a. ammodytes envenomations. Following V. a. ammodytes bite, serial blood counts and coagulation profiles should be performed to help guide Viperfav™ treatment, along with supplemental administration as indicated.